Optimizacija varijanata osiguranja cestovnog prijelaza - Josip Kukec (Promet - Traffic&Transportation, 1970)
By determining the level crossing as a system and structuring the model for forecasting events an attempt has been made to find the optimum levels of securing level crossings. The assessment of the respective level of safety, behavior of road users, local conditions and impact of stochastic regularity with input and output values being determined in an exact manner, a prerequisite has been created for the elaboration of a systematic system analysis. The incidence of emergencies, stopping and waiting times of motor vehicles, utilization C()sts and number and stopping and waiting times of trains have been forecast by mathematical methods and computed by way models. The elaborated algorithm for selection of the optimum level of safety of level crossings creates the possibilities for obtaining reliable elements for decision making in transition from the existing to a newly introduced safety aspect.